Psykiatrins kinesiska encyklopedi: DSM och psykiatrins paradoxala kroppslighet - Grönlund, Anna (K&K - Kultur og Klasse, 2025)
This article uses the concept of neurodivergence as a critical tool to examine the Diagnostic and Statistical Manual of Mental Disorders (DSM) as a taxonomic tool within psychiatry, situating it within broader epistemological and historical contexts. It argues that DSM’s categories do not reflect stable biological entities; rather, they reiterate normative assumptions about mental functioning and pathology. In relation to this, the article highlights psychiatry’s paradoxical relationship to corporeality. Diagnoses are legitimized through a hypothesized biology yet are primarily constructed through discursive frameworks. Focusing on autism as a case study, the article explores how the diagnostic criteria pathologize social and communicative differences while obscuring embodied experiences of suffering. Drawing on phenomenology and critical theory, the article proposes that the concept of neurodiversity may destabilize rigid diagnostic criteria as well as the pathologization of mental differences. Nevertheless, it maintains that an ethical framework for psychiatry must take into account the vast complexity of embodiment without resorting to reductionist biological essentialism. Ultimately, it calls for a non-dualistic approach to psychiatric knowledge and practice, that centers on an ethical diagnostic practice which moves beyond rigid categories while maintaining the alleviation of suffering at the core of psychiatric practice.